Determination of the median lethal concentration (LC50) and efficacy as an anesthetic of eugenol on xiphophorus helleri (Heckel, 1848) (Cyprinodontiformes: poecilidae) - Llanos, Carlos (2012)
The median lethal concentration (CL50) and the anesthetic efficacy of eugenol were determined to diverse doses on the swordfish Xiphophorus helleri (Heckel, 1848). For the determination of the CL50 was used 10 individuals in triplicate in the control and in each concentration. The estimated CL50 to 96 h for eugenol was 22.12 mg.L-1. The efficacy of the anesthesia was carried out in 20 individuals per dose of eugenol. The use of the anesthetic was effective in the doses of 100, 125 and 150 mg.L-1, with a total induction time (T.I.T.) of 265.4 sec to 100 mg.L-1, 229.8 sec to 125 mg.L-1, and 195.9 sec to 150 mg.L-1 and a total recovery time (T.R.T.) of 325.5 sec to 100 mg.L-1, 259.0 sec to 125 mg.L-1, and 246.7 sec to 150 mg.L-1. A greater efficacy to the induction and to the recovery of the anesthesia was obtained at the 125 mg.L-1 concentration by correlation analysis. Logarithmic equations for doses of greater efficiency were obtained: y = 118.1ln(x) + 141.77; R² = 0.5883 (Time of induction vs. Weight to a dose of 125 mg.L-1), y = 401.33ln(x) - 349.75; R² = 0.5786 (Time of induction vs. Length to a dose of 125 mg.L-1), y = 172.22ln(x) + 130.69; R² = 0.4285 (Time of recovery vs. Weight to a dose of 125 mg.L-1), y = 531.62ln(x) - 508.64; R² = 0.3477 (Time of recovery vs. Length to a dose of 125 mg·L-1). Lethal effects were not observed during the induction or recovery of the anesthesia.